Spliceostatins and Derivatives: Chemical Syntheses and Biological Properties of Potent Splicing Inhibitors - Ghosh, Arun K; Mishevich, Jennifer L; Jurica, Melissa S (Journal of natural products (Washington, D.C.), 2021)
Spliceostatins and thailanstatins are intriguing natural products due to their structural features as well as their biological significance. This family of natural products has been the subject of immense synthetic interest because they exhibit very potent cytotoxicity in representative human cancer cell lines. The cytotoxic properties of these natural products are related to their ability to inhibit spliceosomes. FR901564 and spliceostatins have been shown to inhibit spliceosomes by binding to their SF3B component. Structurally, these natural products contain two highly functionalized tetrahydropyran rings with multiple stereogenic centers joined by a diene moiety and an acyclic side chain linked with an amide bond. Total syntheses of this family of natural products led to the development of useful synthetic strategies, which enabled the synthesis of potent derivatives. The spliceosome modulating properties of spliceostatins and synthetic derivatives opened the door for understanding the underlying spliceosome mechanism as well as the development of new therapies based upon small-molecule splicing modulators. This review outlines the total synthesis of spliceostatins, synthetic studies of structural derivatives, and their bioactivity.